A STUDY OF ENGLISH FOOD AND BEVERAGE LEXICONS AT RESTAURANTS AND CAFES IN KUDUS CITY - Fahmi, Syahrul; Riyono, Ahdi; Utomo, Slamet (Universitas Islam Negeri Sunan Gunung Djati, 2025)
This research aims to analyze lexicon choices, word formation, and reference in English culinary lexicon on food and beverage menus in restaurants and cafes in Kudus City. A descriptive qualitative method was employed, collecting data from 25 establishments, Focusing on lexical choices, word formation processes, and references. Semantic theory and morphological analysis were used to interpret the data. The results show that the lexicon contained in the beverage menu is more diverse than the food menu, as beverage variants are used more on menus than food. In addition, compounding is the dominant word formation process found in the menu. The findings illustrate the influence of local culture in the choice of words used on food and beverage menus, as well as showing creative trends in word formation through compounding. This research contributes to the understanding of how the English culinary lexicon is adapted in local cultural contexts and how word formation processes reflect communication needs in the culinary industry, so that people can mention menu names without changing the pronunciation.